2020
DOI: 10.3389/fpsyg.2019.03084
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Executive Functions in 5- and 6-Year-Old Typically Developing Children Through Educational Robotics: An RCT Study

Abstract: Educational Robotics (ER) is a new learning approach that is known mainly for its effects on scientific academic subjects such as science, technology, engineering, and mathematics. Recent studies indicate that ER can also affect cognitive development by improving critical reasoning and planning skills. This study aimed to quantify the ability of ER to empower Executive Functions (EF), including the ability to control, update, and program information, in 5-and 6-year-old children attending first grade, a crucia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…EF include response inhibition skills, working memory, switching, or the ability to flexibly adapt to different tasks, and more complex abilities like planning, which are involved in goal-directed behaviors and problem-solving (Miyake et al, 2000 ; Zelazo et al, 2003 ; Diamond, 2013 ; Viterbori et al, 2017 ). As noted earlier, coding tasks involve problem-solving processes that make significant demands on several levels of EF, including response inhibition, working memory (Shute et al, 2017 ; Di Lieto et al, 2020 ), and planning (Arfé et al, 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EF include response inhibition skills, working memory, switching, or the ability to flexibly adapt to different tasks, and more complex abilities like planning, which are involved in goal-directed behaviors and problem-solving (Miyake et al, 2000 ; Zelazo et al, 2003 ; Diamond, 2013 ; Viterbori et al, 2017 ). As noted earlier, coding tasks involve problem-solving processes that make significant demands on several levels of EF, including response inhibition, working memory (Shute et al, 2017 ; Di Lieto et al, 2020 ), and planning (Arfé et al, 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…When CT skills are practiced, the cited EF processes are also set in motion. Besides showing a strong association between coding abilities and first graders' planning skills (Arfé et al, 2019 , 2020 ), between 5- and 6-year-old children's coding abilities and response inhibition (Arfé et al, 2019 , 2020 ; Di Lieto et al, 2020 ), and between 5- and 6-year-old children's coding abilities and working memory (Di Lieto et al, 2020 ), prior research has also shown the existence of gender differences in the maturation of EF (Unterrainer et al, 2013 ; Grissom and Reyes, 2019 ; Wierenga et al, 2019 ). Although gender differences in executive functioning are not overwhelming (Grissom and Reyes, 2019 ), they are indeed observed in some domains, such as response inhibition and control over impulsive responses.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of artificial cognitive systems has brought numerous novelties to traditional cognitive stimulation and rehabilitation programs. These innovations include complementary programs from home, remote access to platforms and activities, and venturing into gamified, adaptive programs supported with augmented reality mechanisms, virtual reality [ 33 , 34 ], or robotics [ 64 ]. Some included two or more training programs; therefore, from among the 264 articles reviewed, 279 programs were identified, a figure referring to the total of the programs mentioned in all the investigations, although some were implemented in more than one study.…”
Section: Resultsmentioning
confidence: 99%
“…Another non-commercial intervention based on the Corsi block task checked for improvements in visual-spatial WM with transfer to task learning [ 66 ]. The educational robotics intervention Bee-Bot from ER Lab Trainingrobot improved visuospatial WM and inhibition processes [ 64 ]. The Fruit Ninja video game, based on the Go/No go task, improved inhibitory control, transferring to WM and fluid intelligence; electroencephalography (EEG) results indicated an effect on N2; thus, the researchers conclude that response inhibition training appears to potentially improve reasoning ability [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…This result confirmed that inhibition was not sufficiently empowered by the QQQ training or that more intensive and challenging training is required to foster it and generalize the gains to other inhibition tasks. However, it may also be hypothesized that the Simon Says test might not be sensitive enough to detect changes in inhibitory function: in a recent study conducted by Di Lieto and colleagues [ 38 ] on typically developing children attending a first-grade class, a significant effect on inhibition is detected with the Little Frog Test (BIA [ 39 ]) but not with Simons Says.…”
Section: Discussionmentioning
confidence: 99%